Assessing the Effects of Medical Marijuana Laws on Marijuana Use: The Devil is in the Details. (20th October 2014) - Pacula, Rosalie L.; Powell, David; Heaton, Paul; Sevigny, Eric L.
Abstract This paper sheds light on previous inconsistencies identified in the literature regarding the relationship between medical marijuana laws (MMLs) and recreational marijuana use by closely examining the importance of policy dimensions (registration requirements, home cultivation, dispensaries) and the timing of when particular policy dimensions are enacted. Using data from our own legal analysis of state MMLs, we evaluate which features are associated with adult and youth recreational and heavy use by linking these policy variables to data from the Treatment Episode Data Set (TEDS) and National Longitudinal Survey of Youth (NLSY97). We employ differences‐in‐differences techniques, controlling for state and year fixed effects, allowing us to exploit within‐state policy changes. We find that while simple dichotomous indicators of MML laws are not positively associated with marijuana use or abuse, such measures hide the positive influence legal dispensaries have on adult and youth use, particularly heavy use. Sensitivity analyses that help address issues of policy endogeneity and actual implementation of dispensaries support our main conclusion that not all MML laws are the same. Dimensions of these policies, in particular legal protection of dispensaries, can lead to greater recreational marijuana use and abuse among adults and those under the legal age of 21 relative to MMLs without this supply source.